Understanding sustainability in early childhood education case studies and approaches from across the UK - Boyd, Diane; Hirst, Nicky; Siraj-Blatchford, John 1952- (Routledge, 2018)
"This unique book explores research related to education for sustainability within early childhood education in the United Kingdom. Divided into the four home nations, it examines what education for sustainability looks like in practice, discusses the different application and positions of each region, and considers the contribution of early childhood education to support the Sustainable Development Goals"--Provided by publisher.